The implementation of design and build procurement approach in local construction industry - Pang, Sheh Haur (2003)
In our local construction industry, the design and build procurement method had been quite widely used especially on the large and complex project. However, there was little research being conducted on the implementation of this approach in our construction industry. Therefore, this research was aimed to identify the advantages of practicing design and build procurement method. Moreover, the problems/constraints in practicing design and build procurement method will also be studied. Next, the major successes factors in the project practicing design and build procurement method will also be part of this research objective. Finally, this research will also include the study on the effectiveness of the design and build method in shortening the construction time, saving the construction cost and deliver better end product. Survey was conducted through questionnaires distributed among local contractors' firm based in Kuala Lumpur and Selangor state. Upon receiving the feedbacks, SPSS program will be used to analyze it. It was found that the overall performance of design and build approach are in better form. Therefore, this approach should be more widely practiced and not only limited to large and complex projects only.